2005
DOI: 10.1624/105812405x23630
|View full text |Cite
|
Sign up to set email alerts
|

Report of a Staff Program to Promote and Support Breastfeeding in the Care of Vulnerable Infants at a Children's Hospital

Abstract: Ill or premature infants do not have the opportunity to begin breastfeeding in an optimal manner; yet, these infants may benefit most from human milk. Health-care providers' knowledge of breastfeeding in both healthy and ill infants is frequently limited due to deficits in training. This article outlines a multifaceted approach to develop a comprehensive, hospital-wide system to support and promote breastfeeding for vulnerable infants. This approach was designed for the staff of the Children's Hospital of Phil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 29 publications
0
50
0
2
Order By: Relevance
“…Although breast feeding may even be more advantageous in preterm infants, international surveys have shown that only one in three mothers of preterm infants breast feed from birth, and less than 50% of these mothers continue to breast feed their infant until discharge 13 14. In our study, 177 out of 210 mothers of preterm infants started to breast feed from birth, suggesting that our clinic is successful in promoting the breast feeding of preterm infants.…”
Section: Discussionmentioning
confidence: 52%
“…Although breast feeding may even be more advantageous in preterm infants, international surveys have shown that only one in three mothers of preterm infants breast feed from birth, and less than 50% of these mothers continue to breast feed their infant until discharge 13 14. In our study, 177 out of 210 mothers of preterm infants started to breast feed from birth, suggesting that our clinic is successful in promoting the breast feeding of preterm infants.…”
Section: Discussionmentioning
confidence: 52%
“…Likewise, if the average neonatal intensive care unit increased their staffing ratio by 0.15 of a nurse per infant, it could potentially yield an additional 3% of very low birth weight infants being discharged on human milk (i.e., from 48% to 51%), acknowledging that this result was marginally significant ( p = .056). Neonatal intensive care units that provide nurses with the time, resources, and training to develop nurse-led interventions have been shown to improve breastfeeding and human milk rates at discharge (Callen et al, 2005; Pinelli et al, 2001; Spatz, 2011). Beyond organizational investments, a range of potential hospital and unit-level strategies to achieve improved human milk outcomes in the neonatal intensive care unit include training nurses and other health care providers to become lactation certified, developing peer-to-mother breastfeeding counseling networks and lactation focused discharge instruction and support from nurses (Hallowell et al, 2014; Meier et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The constant presence of neonatal intensive care nurses ideally positions them to help mothers overcome challenges related to the establishment of a supply of human milk and breastfeeding. Nursing time invested in helping mothers breastfeed and sustain a milk supply is of paramount importance to very low birth weight infants who receive the greatest nutritional benefits and immunological protection provided in their mother’s milk (Boucher et al, 2011; Hallowell et al, 2014; Ip et al, 2007; Lessen and Crivelli-Kovach, 2007; Nelson, 2007; Spatz, 2004, 2010, 2011; U.S. Department of Health and Human Services, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The family was supported throughout the entire hospital admission by decreasing mother-infant dyad separation and by having her use a hospital-grade breast pump while the infant was taking nothing by mouth. 16 …”
Section: Discussionmentioning
confidence: 99%